2008
DOI: 10.1021/es800633q
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of an Aquatic Predicted No-Effect Concentration for the Synthetic Hormone, 17α-Ethinyl Estradiol

Abstract: 17α-Ethinyl estradiol (EE2) is a synthetic estrogen widely used in combination with other steroid hormones in oral contraceptives and in the contraceptive patch. EE2 has been detected in sewage treatment plant effluents in the low nanogram -per-liter range and occasionally in surface waters in the U.S., U.K., Canada, Brazil, Germany, and elsewhere. The mode of action is receptor-mediated, and estrogen receptors exist in mammals and other vertebrates. A large number of studies on the effects of EE2 on aquatic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(157 citation statements)
references
References 73 publications
8
138
0
10
Order By: Relevance
“…Previous work with several fish species, including the fathead minnow, has documented induction of VTG in male and immature animals by EE2 at water concentrations comparable to those used in this study (for reviews, see U.S. Environmental Protection Agency, 2008;Caldwell et al, 2008). Kang et al (2007) reviewed the effects of BPA on aquatic organisms, and reported induction of VTG in several fish species, including the fathead minnow, at water concentrations similar to or greater than that producing effects in the present study (100 g/L).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous work with several fish species, including the fathead minnow, has documented induction of VTG in male and immature animals by EE2 at water concentrations comparable to those used in this study (for reviews, see U.S. Environmental Protection Agency, 2008;Caldwell et al, 2008). Kang et al (2007) reviewed the effects of BPA on aquatic organisms, and reported induction of VTG in several fish species, including the fathead minnow, at water concentrations similar to or greater than that producing effects in the present study (100 g/L).…”
Section: Discussionmentioning
confidence: 86%
“…First we evaluated whether a third widely studied model AR antagonist, the anti-neoplastic drug cyproterone acetate (CA; Sonneveld et al, 2005), would block TB-induced tubercle formation in fathead minnows in a manner similar to flutamide and vinclozolin. We also conducted mixture studies with TB and 17␣-ethinylestradiol (EE2) or bisphenol A (BPA) which are considered, respectively, strong and weak ER agonists (Kang et al, 2007;Caldwell et al, 2008). Although tubercle formation in fathead minnows is clearly an AR-mediated phenomenon, it is possible that ER agonists could affect development of tubercles in the fathead minnow (Miles-Richardson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The result is 100 or more times less than concentrations (0.13 μg L −1 ) derived from traditional test endpoints with application of assessment factors. 31 …”
Section: Predicted No Effect Concentrations Of Npmentioning
confidence: 99%
“…SSD is a statistical distribution representing the variation in sensitivity of species to a contaminant, and can be developed by a statistical or empirical distribution function of response for a sample of species ( Posthuma et al 2002 ) . This method has been used to assess risks to aquatic organisms and for deriving water quality criteria (WQC) for protecting aquatic species ( Caldwell et al 2008 ;Hall et al 1998 ;Solomon et al 1996 ;Stephan et al 1985 ) . However, because data on the toxicity of contaminants to wildlife are often insuf fi cient, the SSD approach to assess wildlife risks has not often been applied.…”
Section: Methods Of Deriving Trvs and Trcsmentioning
confidence: 99%